2013
DOI: 10.1093/toxsci/kft232
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Causal Reasoning of Hepatic Gene Expression in Rats to Identify Molecular Pathways of Idiosyncratic Drug-Induced Liver Injury

Abstract: Drug-induced liver injury (DILI) represents a leading cause of acute liver failure. Although DILI can be discovered in preclinical animal toxicology studies and/or early clinical trials, some human DILI reactions, termed idiosyncratic DILI (IDILI), are less predictable, occur in a small number of individuals, and do not follow a clear dose-response relationship. The emergence of IDILI poses a critical health challenge for patients and a financial challenge for the pharmaceutical industry. Understanding the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…If compounds with potential mitochondrial liabilities are moved forward, projected exposure will determine a possible safety margin; a mitochondrial liability at 100 µM is a moot point for a compound with a 1-nM efficacy (unless bioaccumulation is afoot). The dilemma of preclinical species not revealing mitochondrial impairment as frank organ toxicity via histopathology requires more refined approaches such as gene expression analysis [34]. The data with diverse mice strains [29] cautions that mitochondrial susceptibility differs which would contribute to idiosyncratic responses.…”
Section: The Futurementioning
confidence: 99%
“…If compounds with potential mitochondrial liabilities are moved forward, projected exposure will determine a possible safety margin; a mitochondrial liability at 100 µM is a moot point for a compound with a 1-nM efficacy (unless bioaccumulation is afoot). The dilemma of preclinical species not revealing mitochondrial impairment as frank organ toxicity via histopathology requires more refined approaches such as gene expression analysis [34]. The data with diverse mice strains [29] cautions that mitochondrial susceptibility differs which would contribute to idiosyncratic responses.…”
Section: The Futurementioning
confidence: 99%
“…In a recent study by Laifenfeld et al [45], a single dose of one of nine IDILI-associated or eight non-DILI-associated drugs was administered to rats at the maximum tolerated dose and gene expression analysis was performed at 24 h. No signs of liver injury assessed by conventional markers were detected. Key molecular pathways involved in mitochondrial injury, inflammation or endoplasmic reticulum stress were identified based on specific gene expression profile signatures by reverse causal reasoning, with 8/9 IDILI-associated drugs but only 4/8 non-DILI-associated drugs.…”
Section: Use Of New Biomarkers In Animal Studiesmentioning
confidence: 99%
“…One of those methods is described by Laifenfeld et al 54 The authors conducted gene expression studies in rats treated with idiosyncratic DILI compounds and causal reasoning identified fingerprints indicative of DILI, but were absent in compounds not known to cause DILI. 54 For DILI compounds inhibiting BSEP, the hunt for biomarkers suitable for rat and dog continues. Whether bile salt profiles can help identify potential human risk remains to be seen in the coming years.…”
Section: Less-dili Drugsmentioning
confidence: 99%